Epigenetic Modification of OXTR is Associated with Openness to Experience - Haas, Brian W. (Personal Neurosci, 2018)
Oxytocin is a neuropeptide known to influence social and cognitive processing across several mammalian species. There currently exists a mixed and controversial pattern of evidence that oxytocin pathway genes confer individual differences in social cognition and personality in humans. Inconsistencies across studies may in part be explained by the presence of intermediary, epigenetic, variables that exist between genotype and phenotype. This study was designed to investigate the association between epigenetic modification of the Oxytocin Receptor Gene (OXTR), via DNA methylation, and Big-5 personality traits. Genetic data were collected via saliva samples and analyzed to quantify DNA methylation within the promoter region of OXTR. The results indicate that Openness to Experience is associated with OXTR DNA methylation, while controlling for the remaining Big-5 personality dimensions (Neuroticism, Extraversion, Agreeableness, and Conscientiousness) and sex and age. This finding provides additional support for models associating oxytocin with individual differences in personality and identity in humans.